Health behaviors in a group of women treated surgically for breast cancer and selected clinical and socio-economic parameters - Michalik, Joanna; Rząca, Marcin; Stanisławek, Andrzej; Wolski, Dariusz; Węgorowski, Paweł (Journal of Education, Health and Sport, 2018)
Introduction Breast cancer is the most common malignancy in women, accounting for nearly 1.7 million cases and over 0.5 million deaths worldwide. The basic solution is surgical treatment. The execution or closing of the variometer ends with the element of unpicking. Objective The ability to fight cancer is ongoing. Analyzed declared costs in the economic variety. Materials and methods The study was provided by a patient from Lublin in 2016. The concept of a diagnostic survey was used. Old planm and questionnaire. IZZ) by Z. Juczyński. Results In order to obtain the correct result, the following criteria should be applied: IZZycie 90.41 points, which corresponds to the standard 7-10 stena and is interpreted as a high result. Conclusions Patients admitted to the Lublin Oncology Center for treatment of breast cancer. In the studies, the most sensitive were psychological attitude and the lowest eating habits. In the time of interest, eating habits were not such statistical information. Key words: breast cancer, health behaviors